ANALISIS DIAGNOSTIK KESULITAN SISWA KELAS V DALAM MENENTUKAN IDE POKOK DAN MEMBERIKAN SOLUSI LOGIS BERDASARKAN TEKS LITERASI BAHASA INDONESIA - Shofyani Salasa; Dian Armanto; Anita Yus (STKIP Subang, 2026)
High-level literacy skills, particularly in determining main ideas and providing logical solutions, serve as a crucial foundation for elementary school students. This study aims to describe the difficulty profile of fifth-grade students in determining main ideas and to evaluate the quality of the test instruments used as a basis for instructional improvement. The research method employed is a descriptive quantitative approach involving fifth-grade elementary students as subjects. The research instrument consists of written tests featuring explanatory and narrative texts on environmental and cultural themes, classified based on Bloom's Taxonomy cognitive levels (C1-C6). The results indicate a significant imbalance in ability distribution, with 50% of students falling into the